The effect of dietary fish oil replacement with soybean oil on growth and health of dusky kob, Argyrosomus japonicus (Pisces: Sciaenidae) - Rossetti, Nani Adami (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Lipids are essential components for fish because they contain fatty acids that are vital for regular growth and health. Fish oil is rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which are essential fatty acids for carnivorous fish, and therefore this product has traditionally been used as the main source of lipids in fish feeds. However, with declining fisheries resources worldwide and the rapid expansion of the aquaculture industry pressuring this finite resource, such ingredients are becoming less available and more expensive. It is therefore necessary to explore the utilization of ingredients that are sustainable and competitive alternatives to fish oil in marine finfish feeds. This work investigated the effects of the substitution of fish oil with soybean oil on the growth performance, feed efficiency, fatty acid composition of the liver tissue and some health parameters in juvenile dusky kob, Argyrosomus japonicus; an increasingly popular sciaenid marine aquaculture species in South Africa. Six diets (18 % total lipid and 46 % protein) with increasing percentage substitution of fish oil with soybean oil (1, 14, 28, 42, 56 and 70 %) were fed to juvenile kob. After 84 days of feeding these diets to the fish, no significant differences in fish length and weight between treatments were observed. However, there was a significant trend of a decrease in specific growth rate, ranging from (Â± standard error) 0.87 Â± 0.06 to 0.72 Â± 0.04 % body weight dayâ »Â¹, and condition factor, ranging from 1.59 Â± 0.03 to 1.54 Â± 0.02, with increasing vegetable oil replacement in the diets between days 56 and 84. There were no differences in red blood cell count, haematocrit and haemoglobin concentration after 206 days of feeding. However, visceral fat index (VFI) increased significantly from 1.08 Â± 0.17 % for fish fed diets with 28 % soybean oil, to 2.24 Â± 0.15 % for fish fed diets with 70 % soybean oil. Similarly, hepatosomatic index (HSI) increased significantly from 0.84 Â± 0.08 % to 1.80 Â± 0.12 % in the control diet and the 56 % soybean oil diet, respectively. After 206 days of feeding, fish fed diets with 42 to 70 % soybean oil showed greater number of lipid vacuoles in the liver, which were also larger in size, and hepatocytes nuclei were displaced to the cell periphery. The fatty acid composition of the liver tissue strongly corresponded to the fatty acid composition of the diets. Linoleic acid accumulated in the liver of the fish fed increasing soybean oil in the diets. In contrast, EPA and DHA decreased from 13.63 to 1.97 %, and 14.34 to 3.28 %, respectively, in the liver tissue of fish fed diets with increasing soybean oil content; consequently the n-3/n-6 ratio was also significantly reduced with inclusion of vegetable oil in the diets. The trend of decreasing growth rate with increasing oil replacement towards the end of the trial corresponds with increases in VFI, HSI, as well as the fatty acid accumulation and lipid vacuoles in the liver. This suggests that dusky kob is less able to metabolise soybean oil at increased substitution levels which would account for the poorer growth at higher levels. The dependence of fish on dietary marine oil decreased significantly with each inclusion of soybean oil in the diets. Nonetheless, the calculations based on the nutrient ratio presented positive outcomes for all treatments, that is, values of marine oil dependency ratio were below one for all treatments. It is concluded that soybean oil can replace fish oil in formulated diets for dusky kob up to a level of 28 % of total dietary lipids, as evidenced by the good growth and feed efficiency, and no apparent negative health effects observed up to this level.
Keywords: Sciaenidae; Fish culture; Argyrosomus -- Growth; Argyrosomus -- Feeding and feeds; Argyrosomus -- Health; Fish oils as feed; Soy oil; Lipids; Eicosapentaenoic acid; Docosahexaenoic acid